Faktor-faktor yang berkaitan mutu penjagaan pesakit yang menjalani pembedahan utama di Hospital Universiti Sains Malaysia - Mohamad Nor, Nurhayati (2015)
This study was conducted to determine the factors that affect the quality of patient care in the Hospital USM Kubang Kerian, Kelantan. A total of 145 nurses and 75 patients is involved in this study. The questionnaire which consists of nurse workload index (NWI-R) and environmental complexity scale (ECS) was distributed to be completed by the nurses. Meanwhile, the number of hours for patient care was assessed by using checklist PRN – 80. The objective of this study was to investigate the factors which affect the quality of patient care who undergo major surgery at Hospital USM. Statistical method that was used to test the hypothesis were frequency, reliability test and spearman correlation. The result illustrated that work satisfaction at moderate level was 62.8% and no changes in quality of patient care was 53.1%. The highest maltreatment experienced by nurses was in terms of emotional, 47.6% and 27.9% was caused by their colleagues. The highest average workloads of nurses was 6.30 for nursing autonomy, nursing leadership was 6.20, 6.15 for control over nursing practice, 5.81 for relationship between nurses and doctor and 4.33 for adequate resources. The result also showed that 79.3% of the workloads increased when there were students in the ward, while 73.9% showed that there were patient acuity changes and 68.2% was when it is necessary to perform work reorganisation. There was a correlation between patients’ demographics and nurses’ workloads (r = -0.429, p<0.01), the correlation between patient acuity changes and communication with the doctors was significant (r = 0.385, p<0.01) and the delay of the procedures to the patients (r = 0.449, p<0.01). There was also a significant correlation between emergency leave and dissatisfaction with the current task (r = -0.169, p<0.05) and also intention to leave the profession (r = 0.169, p<0.05). Besides that, there was a significant correlation for the factors of autonomy and physical harm (r = -0.245, p<0.01) and also threats (r = -0.217, p<0.01). The relationship between nurses and doctors was significant with physical harm (r = -0.313, p<0.01) and threats (r = - 0.261, p<0.01). Other than that, the correlation between the task which was performed late and physical threats was significant (r = -0.186, p<0.05) and threats (r = -0.232, p<0.01). There was also a significant correlation between the task which was not done during the shifts and physical harm (r = 0.221 p<0.01), threats (r = 0.210, p<0.05) and emotional abuse (r = 0.236, p<0.01). The intention to leave the profession showed a significant correlation with physical abuse (r = 0.227, p<0.01) and threats (r = 0.225, p<0.01). In conclusion, workloads and nursing working environment affect the quality of patient care.